Relación entre la inversión pública y el sector construcción del departamento de Loreto periodo 2017 - 2021 - Pinedo Chávez, Diego Angel (2023)
Public investment is very necessary for the development of the country, and the department of Loreto does not escape this premise. This magisterial thesis has as objective The objective of the present investigation is to determine the relationship between public investment and the Construction sector of the department of Loreto in the period 2017 - 2021. That is why this research of Quantitative type, Correlational level and of non-experimental design. Once the discussion of the results has been carried out, it is concluded that there is a direct relationship between public investment and the behavior of the Construction sector of the department of Loreto, studied in the period 2017 - 2021; statement endorsed by the results of the statistical test, where the Correlation Coefficient was r = 0.988585235; and the Coefficient of Determination of R2 = 0.977300768; which shows a very good statistical association between the study variables, as well as determination. The public investment analyzed by levels of government, shows that it was led by the Regional Government having executed the sum of S/. 1,915.10 million, which represents 37.04% of the total amount. The Transport and Communications function concentrates public investment, having dedicated the value of S/. 1,949.90 million, equivalent to 37.71% of the total investment. The value generated by the Construction sector had a variable behavior during the five years, being on average S/. 328.33 million per year.